Pengaruh Nilai Produk, Kesadaran Merek, Persepsi Harga, dan Green Marketing terhadap Minat Beli Konsumen Minyak Nilam Organik - Geta Ambartiasari; Hazful Maizi; Chairuni AR (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of Product Value, Brand Awareness, Price Perception, and Green Marketing on Consumer Purchase Intention toward Organic Patchouli Oil. The research is motivated by the growing public awareness of environmental issues and the increasing importance of sustainable marketing strategies in shaping consumer purchasing decisions. A quantitative approach was employed by distributing questionnaires to 80 respondents who are potential consumers of organic patchouli oil in Indonesia. Each variable was measured using a five-point Likert scale and analyzed through multiple linear regression using SPSS software. The results show that all independent variables have a positive and significant effect on purchase intention, with Green Marketing emerging as the most dominant factor. The coefficient of determination (R²) of 0.682 indicates that 68.2% of the variation in purchase intention is explained by the four variables, while the remaining 31.8% is influenced by other factors outside the model. These findings highlight the importance of implementing consistent green marketing strategies, strengthening brand awareness, and delivering relevant product value to enhance consumer interest and the competitiveness of organic patchouli oil in the environmentally friendly product market.